Dietary Patterns and Physical Activity on Nutritional Status of Science Faculty Students, Universitas Negeri Makassar - Taiyeb, A. Mushawwir; Saru, Amaliah Amriani Amran (Journal of Scientific Insights, 2025)
Nutritional status is an important health indicator influenced by multiple factors. Students aged 19–24 years remain in a growth phase and require adequate nutrition and healthy lifestyle habits to support academic performance and long-term wellbeing. This study aimed to examine the effects of dietary patterns and physical activity on the nutritional status of Biology Department students at the Faculty of Mathematics and Natural Sciences, State University of Makassar. An analytic observational study with a cross-sectional design was conducted among 115 students. Dietary patterns were assessed using an FFQ questionnaire, physical activity using the GPAQ, and nutritional status using BMI measurements. Data were analyzed using Chi-square tests and multiple linear regression. Results showed that 53.9% of students had poor dietary patterns, while 63.5% had high levels of physical activity. Both dietary patterns and physical activity were significantly associated with nutritional status (p < 0.001). Regression analysis indicated that dietary patterns had a significant positive effect on nutritional status, whereas physical activity had a significant negative effect. The model explained 81.6% of the variation in nutritional status (R² = 0.816). In conclusion, dietary patterns and physical activity significantly influence students nutritional status. Interventions should emphasize improving dietary habits and promoting physical activity to maintain optimal nutritional health.